Political Factors Mediating between Attitude and Tax Compliance among Merchants in Peruvian Shopping Centers - Mayta-Huiza, Dora Amalia; Flores-Huamán, Ruth; Vargas-Apaza, Silver Luis; Chávez-Choque, Melina Elizabeth; Pineda-Yucra, Wilfredo; Guevara-Gómez, Hilda Elizabeth; Bermejo-Peralta, Luis Delfín (Migration Letters, 2023)
The objective is to know the effect of political factors between the tax attitude and the fulfillment of tax obligations of merchants of shopping centers in the city of Cusco. It is a basic, non-experimental, causal explanatory research of cross-sectional observational design, 230 merchants selected in probabilistic sampling participate and answer a structured questionnaire on personal, commercial and tax characteristics, awareness, knowledge and tax obligations, the data are analyzed using the PLS-SEM technique. The results show the validation of the construct measurement model. The personal, commercial and tax management characteristics of the merchants are very primary, 100% are personal enterprises, they are associated with the shopping center, 97.40% sell monthly average less than S/. 5,000.00, 97.50% are under the New RUS tax system and 57.83’% are new businesses are less than five years old, These experiences are background that develop tax knowledge at regular level. In the analysis of the structural theoretical model it is determined that there are total direct effects of tax attitude and tax compliance established by the standardized beta coefficient of 0.273 the total indirect effects is βt=0.207, the R2 = 0.043 and p=0.000 < 0.05. Conclusion. The political factors of trust in the state and received equity are mediating variables that have a positive and significant influence between the tax attitude and tax compliance of the merchants of the commercial centers of Cusco.